Phyto-oxylipin mediated plant immune response to colonization and infection in the soybean-Phytophthora sojae pathosystem - Adigun, Oludoyin Adeseun; Pham, Thu Huong; Grapov, Dmitry; Nadeem, Muhammad; Jewell, Linda Elizabeth; Cheema, Mumtaz; Galagedara, Lakshman; Thomas, Raymond (Frontiers in Plant Science, 2023)
Food security is a major challenge to sustainably supply food to meet the demands of the ever-growing global population. Crop loss due to pathogens is a major concern to overcoming this global food security challenge. Soybean root and stem rot caused by Phytophthora sojae results in approximately 2B US crop loss annually. Lipid mediated plant immunity is a very attractive target for developing long term resistance in many plant disease pathosystem. However, little is known about the phyto-oxylipin’s role in the successful strategies used by tolerant soybean cultivar to mitigate Phytophthora sojae infection. We used scanning electron microscopy to observe the alterations in root morphology and a targeted lipidomics approach using high resolution accurate mass tandem mass spectrometry to assess phyto-oxylipin anabolism at 48 h, 72 h and 96 h post infection. We observed the presence of biogenic crystals and reinforced epidermal walls in the tolerant cultivar suggests a mechanism for disease tolerance when compared with susceptible cultivar. Similarly, the unique biomarkers of oxylipin mediated plant immunity [10(E),12(Z)-13S-hydroxy-9(Z),11(E),15(Z)-octadecatrienoic acid, (Z)-12,13-dihydroxyoctadec-9-enoic acid, (9Z,11E)-13-Oxo-9,11-octadecadienoic acid, 15(Z)-9-oxo-octadecatrienoic acid, 10(E),12(E)-9-hydroperoxyoctadeca-10,12-dienoic acid, 12-oxophytodienoic acid and (12Z,15Z)-9, 10-dihydroxyoctadeca-12,15-dienoic acid] generated from intact oxidized lipid precursors in a tolerant soybean cultivar relative to infected susceptible cultivar and non-inoculated controls at 48 h, 72 h and 96 h post infection by Phytophthora sojae. While microbial origin oxylipins, 12S-hydroperoxy-5(Z),8(Z),10(E),14(Z)-eicosatetraenoic acid and (4Z,7Z,10Z,13Z)-15-[3-[(Z)-pent-2-enyl]oxiran-2-yl]pentadeca-4,7,10,13-tetraenoic acid were upregulated only in infected susceptible cultivar but downregulated in infected tolerant cultivar. These unique biomarkers maybe used in tolerant cultivar as a mechanism for disease tolerance. This study demonstrated novel evidence for phyto-oxylipin metabolism in soybean cultivars during pathogen infection and this evidence may be a potential application in further elucidation of the role of phyto-oxylipin anabolism in soybean tolerance to Phytophthora sojae infectionn